HIV-Related Immune Activation and Inflammation: Current Understanding and Strategies - Tingxia Lv; Wei Cao; Taisheng Li (Journal of Immunology Research)
Although antiretroviral therapy effectively controls human immunodeficiency virus (HIV) replication, a residual chronic immune activation/inflammation persists throughout the disease. This aberrant immune activation and inflammation are considered an accelerator of non-AIDS-related events and one of the driving forces of CD4+ T cell depletion. Unfortunately, HIV-associated immune activation is driven by various factors, while the mechanism of excessive inflammation has not been formally clarified. To date, several clinical interventions or treatment candidates undergoing clinical trials have been proposed to combat this systemic immune activation/inflammation. However, these strategies revealed limited results, or their nonspecific anti-inflammatory properties are similar to previous interventions. Here, we reviewed recent learnings of immune activation and persisting inflammation associated with HIV infection, as well as the current directions to overcome it. Of note, a more profound understanding of the specific mechanisms for aberrant inflammation is still imperative for identifying an effective clinical intervention strategy.